Motivations for Participation in Parkinson Disease Genetic Research Among Hispanics versus Non-Hispanics - Nuytemans, Karen; Manrique, Clara P.; Uhlenberg, Aaron; Scott, William K.; Cuccaro, Michael L.; Luca, Corneliu C.; Singer, Carlos; Vance, Jeffery M. (Frontiers in Genetics, 2019)
Involvement of participants from different racial and ethnic groups in genomic research is vital to reducing health disparities in the precision medicine era. Racial and ethnically diverse populations are underrepresented in current genomic research creating bias in result interpretation. Limited information is available to support motivations or barriers of these groups to participate in genomic research for late onset, neurodegenerative disorders. To evaluate willingness for research participation, we compared motivations for participation in genetic studies among 113 Parkinson Disease (PD) patients and 49 caregivers visiting the Movement Disorders clinic at the University of Miami. Hispanics and non-Hispanics were equally motivated to participate in genetic research for PD. However, Hispanic patients were less likely to be influenced by the promise of scientific advancements (N=0.01). This lack of scientific interest, but not other motivations, was found to be likely confounded by lower levels of obtained education (N=0.001). Overall, these results suggest that underrepresentation of Hispanics in genetic research may be partly due to reduced invitations to these studies.